When is lead screening appropriate in adolescents?. Issue 8 (August 2016) - Proctor, Ben; Palombo, David; LeBato, Alan
Abstract : Evidence‐Based Answer : Screen adolescents for lead poisoning only if they are an immigrant or foreign adoptee between the ages of 6 months and 16 years. Routine screening of adolescents is not indicated (SOR: C, based on expert opinion).